A real-world data analysis of ocular adverse events linked to anti-VEGF drugs: a WHO-VigiAccess study - Li, Chen; Lu, Yicheng; Song, Ziyue; Liu, Yueqi (Frontiers in Pharmacology, 2024)
Introduction Vascular endothelial growth factor (VEGF) is key to wet age-related macular degeneration (wAMD). Anti-VEGF drugs are the main treatment in clinics. This study assessed ocular adverse events (AE) from anti-VEGF drugs in VigiAccess, WHO’s database, and compared adverse drug reaction (ADR) profiles of four drugs to aid personalized treatment choices for optimal benefit and safety. Methods The design was a descriptive retrospective study. We observed four anti-VEGF drugs commonly used in the clinical treatment of wAMD, and their ADR reports came from WHO-VigiAccess. The collected data included the age group, gender, and regional data, as well as the data of disease systems and symptoms caused by ADR recorded in the annual ADR reports and reports received by the WHO. We observed the overall characteristics of the ADR reports of these drugs, then explored the distribution of 27 SOCs of these drugs. Subsequently, we compared the most common ocular ADRs of the drugs. Finally, we compared the commonalities and differences of ocular ADRs related to the drugs. Results Overall, 57,779 AE associated with the four anti-VEGF drugs were reported. The results showed that the number of females experiencing ADRs (67.83%) was significantly higher than males (32.17%), the age group with the highest reported incidence was over 75 years old. More than half of the ADR reports came from the Americas (50.86%). The five most common types of AE were: eye disorders (43.56%), general disorders and administration site conditions (34.47%), injury poisoning and procedural complications (13.36%), infections and infestations (11.61%), nervous system disorders (9.99%). Compared with the other three inhibitors, brolucizumab had a significantly higher rate of ocular ADR reports. The most common ocular ADRs of these four anti-VEGF drugs were mostly related to visual impairment, vision blurred, and blindness. However, there is still a disparity of ADRs between different drugs. Conclusion The presence of ocular AEs when using anti-VEGF drugs to treat wAMD in clinical practice should attract clinical attention. Clinicians should use these expensive drugs more rationally based on the characteristics of ADRs and develop personalized treatment plans for patients.